A case of torsion of the wandering spleen presenting as hypersplenism and gastric fundal varices - Kader Irak; İrfan ESEN and Murat Keskin and Ahmet Tarık Eminler and Talat AYYILDIZ and Ekrem Kaya and Murat KIYICI and Selim GÜREL and Selim Giray Nak and Macit GÜLTEN and et al. (Turkish Journal of Gastroenterology, 2019)
-